A biomechanical method for the evaluation of sports techniques by standard motion, motion variability and motion deviation - Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The essential but most difficult steps in an optimization loop of sports techniques are the evaluation and diagnosis of the techniques of students and/or athletes, and the identification of their technical faults and limiting factors. This process is frequently referred to as technique analysis in sport biomechanics but the concept of technical analysis is less well developed. Teachers and coaches frequently adopt a model technique or a template of model performance approach in which sequential pictures and figures of an outstanding athlete or skilled performer are used as a motion pattern model. This paper proposes a biomechanical method for the evaluation of sports techniques in which an averaged motion pattern of skilled performers is used as a standard motion, and motion variability and motion deviation are employed as indices to identify critical technical points and faults of an athlete.